0570 Dose Titration Of Solriamfetol In Participants With Obstructive Sleep Apnea From A 6-week Randomized-withdrawal Trial. (12th April 2019) - Strollo, Patrick J; Schwab, Richard; Hedner, Jan; Collop, Nancy; Chen, Dan; Carter, Lawrence P; Bujanover, Shay; Menno, Diane; Black, Jed; Pepin, Jean-Louis; Redline, Susan
Abstract: Introduction: Solriamfetol significantly reduced participant-reported excessive daytime sleepiness relative to placebo in two randomized, fixed-dose phase 3 trials involving participants with narcolepsy or OSA. Dosing trends from a phase 3, 6-week, placebo-controlled, randomized-withdrawal study that involved a clinical titration were explored, including whether baseline characteristics were associated with dose titration. Methods: Inclusion criteria were adults (≥18y) with OSA; Epworth Sleepiness Scale (ESS) score ≥10; Maintenance of Wakefulness Test mean sleep latency <30 minutes; and current or past use of primary OSA therapy. Dosing started at 75 mg once daily, and participants were able to titrate up or down 1 dose level (other doses included 150 and 300 mg/day) every 3 days following a scheduled consultation with their clinician to reach an efficacious and tolerable dose by end of the 2-week dose-titration phase. After the dose-titration phase, participants then entered a 2-week, open-label stable-dose phase, during which dose adjustments were not allowed. In these post hoc analyses, dose changes during the dose-titration phase and participant characteristics were examined by the final dose to which they were titrated. Results: 174 subjects were enrolled and 157 entered the stable-dose phase at a dose of 75 mg (14.6%), 150 mg (31.8%), or 300 mg (53.5%). Seventeen subjects discontinued in the dose-titration phase with 5 due to adverse effects. More female participants were titrated to 75 mg (56.5% of participants in the 75-mg group) relative to the other doses (33%-38% female) and the overall study population (38%). By day 9, 68.2, 50.0, and 78.6% of participants who were eventually titrated to 75, 150, and 300 mg, respectively, had reached their stable dose. At the end of the stable-dose phase, the percentage of participants who reported improvement on the PGI-C was ≥75% in all groups (91.3% 75 mg, 88% 150 mg, 75% 300 mg). Conclusion: Most participants reached a stable dose in less than 2 weeks. The majority of participants were titrated to the 300-mg dose. There were marked improvements across doses on the PGI-C. Support (If Any): Jazz Pharmaceuticals.